2005
DOI: 10.1111/j.1742-1241.2005.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ramadan on demographics and frequencies of disease-related visits in the emergency department

Abstract: Summary The objective of this study was to determine whether Ramadan is changing frequencies and demographics of visits due to certain diseases. Data obtained from the charts of the adult patients admitted into the emergency department (ED) due to 10 predetermined entities between 2000 and 2004 were analysed. Demographic variables analysed separately for certain entities visiting the ED in Ramadan were not found to be different from visits in other times of year. Visit frequencies for hypertension and uncompli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 9 publications
1
41
0
Order By: Relevance
“…When examining the higher quality studies (those rated 7 or higher on a 1-10 scale), 24 (62%) reported lower BP or less hypertension among those who were more R/S [161][162][163][164][165][166][167][168][169][170][171][172][173] or in response to a R/S intervention [174][175][176][177][178][179][180][181][182][183][184] (including two reports from a single study, one reporting results for the overall sample and one for the sample stratified by race). In contrast, seven studies reported higher blood pressure among the more religious, including two lower quality studies [185,186] and five high-quality studies (13%) [187][188][189][190][191]. Why would R/S would be associated with higher blood pressure?…”
Section: Hypertensionmentioning
confidence: 82%
“…When examining the higher quality studies (those rated 7 or higher on a 1-10 scale), 24 (62%) reported lower BP or less hypertension among those who were more R/S [161][162][163][164][165][166][167][168][169][170][171][172][173] or in response to a R/S intervention [174][175][176][177][178][179][180][181][182][183][184] (including two reports from a single study, one reporting results for the overall sample and one for the sample stratified by race). In contrast, seven studies reported higher blood pressure among the more religious, including two lower quality studies [185,186] and five high-quality studies (13%) [187][188][189][190][191]. Why would R/S would be associated with higher blood pressure?…”
Section: Hypertensionmentioning
confidence: 82%
“…Coffee and strong tea consumption is highly abundant in Bedouin culture and withdrawal is probably prominent. A previous [9] study has demonstrated higher rates of headache-related emergency room visits during Ramadan in Muslim communities in India. In addition, no epidemiological migraine surveys were preformed in the Bedouin community, our clinical experience is that migraine prevalence and characteristics are similar among Bedouins to the Jewish community.…”
Section: Discussionmentioning
confidence: 99%
“…A MEDLINE search of articles containing the word 'Ramadan' or a combination of 'fasting' plus either 'Muslim' or 'Islam' found that researchers have examined the effect of fasting during Ramadan on diabetes (Salti et al 2004, Sari et al 2004, breast milk composition (Rakicioglu et al 2006, Rashid 2007, cholesterol levels (Adlouni et al 1998, Qujeq et al 2002, seizure activity (Gomceli et al 2008), incidence of acute cardiac events (Al suwaidi et al 2004a), incidence of hospitalisation for congestive heart failure (Al Suwaidi et al 2004b), frequency of emergency department visits (Topacoglu et al 2005) and neonatal birth weight (Kavehmanesh and Abolghasemi 2004). Several studies have noted inadequate hydration (Schmahl andMetzler 1991, Leiper andMolla 2003); variations in nutritional intake (Gharbi et al 2003, Lamine et al 2006, Reilly and Waterhouse 2007; challenges with medication, administration and adherence (Aadil et al 2004, Habib et al 2008; and inadequacy of sleep (Roky et al 2003) during Ramadan.…”
Section: Introductionmentioning
confidence: 99%